2013
DOI: 10.7860/jcdr/2013/6712.3733
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25(OH) D in Diabetes Mellitus Type 2: Relation to Glycaemic Control

Abstract: Introduction: There is increasing evidence on association between vitamin D insufficiency and diabetes, but the impact of vitamin D status on glycaemic status and vice versa, has not been well reported. Our aim was to investigate the level of 25-hydroxyvitamin D(25(OH)D) and the prevalence of vitamin D abnormalities in patients with diabetes mellitus (DM) type2 and in those without diabetes; and to ascertain the impact of 25(OH)D levels on glycaemic control and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 11 publications
(11 reference statements)
11
48
1
1
Order By: Relevance
“…We found a significant weak negative correlation between HbA1C and 25(OH)D, similar to other previously published studies [12, 18, 23, 28, 33, 34]. However glycemic control was not associated with vitamin D when we controlled for confounding factors, as verified by Luo et al and Al-Shoumer et al [35, 36].…”
Section: Discussionsupporting
confidence: 91%
“…We found a significant weak negative correlation between HbA1C and 25(OH)D, similar to other previously published studies [12, 18, 23, 28, 33, 34]. However glycemic control was not associated with vitamin D when we controlled for confounding factors, as verified by Luo et al and Al-Shoumer et al [35, 36].…”
Section: Discussionsupporting
confidence: 91%
“…The HbA1c levels were uncontrolled in about 82% of patients enrolled in this study, and our results were in agreement with many studies which reported high HbA1c levels in T2DM …”
Section: Discussionsupporting
confidence: 93%
“…Recently, there are compelling evidences suggesting that vitamin D deficiency might also play a significant role in the pathogenesis of type 2 diabetes mellitus 21,22 . Typically, serum 25(OH)D concentrations are low in type 2 diabetes patient 23 , particularly among those with poor glycemic control and long diabetes durations 24 Then it was observed that oral administration of 1, 25(OH) 2 D 3 completely protects NOD mice from insulin-dependent diabetes 29 . However, it is not known whether 1, 25(OH) 2 D 3 can actually inhibit β-cell apoptosis.…”
Section: A N U S C R I P Tmentioning
confidence: 98%